Targeting P2X7 receptors as a means for treating retinal disease. Issue 8 (August 2019) - Fletcher, Erica L.; Wang, Anna Y.; Jobling, Andrew I.; Rutar, Matthew V.; Greferath, Ursula; Gu, Ben; Vessey, Kirstan A.
Highlights: P2X7 has multiple actions depending on the level of exposure to extracellular ATP. Major retinal diseases are attributed to excessive activation of P2X7 receptors. The crystal structure of P2X7 has recently been characterized. Brain-permeant P2X7 receptor blockers have potential for treating retinal disease. Abstract : Age-related macular degeneration and glaucoma are the commonest causes of irreversible vision loss in industrialized countries. The purine ATP is known to regulate a range of cellular functions in the retina via its action on P2 receptors, especially the P2X7 receptor. Although agents that attenuate P2X7 receptor function have been in development for many years, no compound is currently approved for the treatment of eye disease. However, newer compounds that cross the blood–brain barrier could have potential to reduce vision loss. This review will outline recent information relating to the role of P2X7 in age-related macular degeneration and glaucoma and, subsequently, we will discuss recent developments for attenuating P2X7 receptor function.